Avaliação da qualidade do ar em escolas fundamentais da cidade de Colombo através de material particulado em suspensão e sua relação com a indústria local da cal - Alves, Ricardo (2009)
Adverse health effects of ambient air pollution in general, and specifically airborne particulate matter (PM), have drawn considerable attention in the last years. Epidemiological studies have shown an association between respiratory related mortality and morbidity and ambient PM with different diameters. Specifically, air pollution caused by the lime production industry has become a serious problem with potential effects to human health, especially in developing countries. Colombo is a city included in the Metropolitan Region of Curitiba (capital of Paraná State) in South Brazil, where a correlation has been shown between the lime production and the number of persons who need respiratory treatment in a local hospital. As school-age children spend large time inside school buildings, the potential health consequence of lime contaminants in primary schools has been investigate in order to determine the children’s exposure to this contaminant. In order to assess the indoor air quality, three primary schools were selected from the whole city to characterize the particulate matter pollutants indoors and outdoors of the classrooms, and related it to children’s respiratory sickness. Information concerning the bulk composition was provided by energy-dispersive x-ray fluorescence (EDXRF). From the calculated indoor/outdoor ratios and the enrichment factors it was observed that Ca-, S-, Cl-, Pb and As-rich particles are of concern in the indoor environment. In the present research, the chemical compositions of individual particles were quantitatively elucidated, including low-Z components like C, N and O, as well as higher-Z elements, using automated electron probe microanalysis low Z EPMA. Samples were further analysed for chemical and morphological aspects, determining the particle size distribution and classifying them according to elemental composition associations. In order to investigate effects of inhaled air pollutant, spirometry measurements on elementary schoolchildren were done. The majority of the respirable particulate matter identified was composed of aluminosilicates, CaMg oxides, biogenic particles, sulphur-rich particles and soot. In view of the density and aerodinamic diameter of the aerosol particles, local deposition efficiencies in the children and human respiratory system were calculated, revealing the deposition of CaMgO and soot at pulmonary levels is higher in children than adults. The deposition pulmonary percentage of particulate matter of fine CaMgO reaches 18 and 25% to adults and children respectively, while for coarse fraction is 6% in both. The deposition percentage of fine soot in the pulmonary region reaches 10 e 12% to adults and children respectively, while for coarse fraction the percentage is 18% in both cases. Spirometric data have not shown differences between groups. A self-administered questionnaire, adapted from the International Study of Asthma and Allergies in Childhood (ISAAC), distributed to the pupils showed just the 2008 dataset slight differences in the prevalence of respiratory symptoms. The results of this study offer evidence of the threat that these types of particles pose inside the classrooms, allowing mitigation strategies of the school direction and policy-makers.